Multiwalled carbon nanotubes and zinc oxide using a high energy milling method for radar-absorbent. (4th February 2022) - Kholil, Muhamad Abdul; Priyono, Priyono; Subagio, Agus
Abstract: Radar is a technology that is always used by the military to detect an object because it can determine the shape, size, position, distance, and speed of an object. This enables the national defence system to have anti-radar technology to protect defence equipment or other important defence objects. One way that can be applied is using radar-absorbing material to coat the surface of the object. A good radar-absorbing material is made of a combination of dielectric materials with magnetic materials. MWCNT/ZnO composites were produced by a high energy milling method. The various milling times (0, 1, 3 and 5 h) using HEM on the microwave absorbing properties of the composites has an effect, which was studied. The experimental results show that the optimum microwave absorption ability is reached when the HEM process is carried out for 5 h with a thickness of 2.0 mm. The optimum return loss is −26.4 dB at a frequency of 11.2 GHz and the bandwidth correlative to the return loss is below −10 dB with a frequency greater than 1.5 GHz. When comparing MWCNT/ZnO without HEM treatment, the results show that HEM treatment can also increase microwave absorption properties.